Politik Uang Dalam Dinamika Sosial Di Sumatera Barat Dan Implikasinya Terhadap Ketahanan Wilayah - Putra, Eka Vidya; Fernandes, Reno; Patra, Haldi (Jurnal Ketahanan Nasional, 2024)
This study aimed to explored the relationship between money politics and regional political in the context of changing social dynamics in West Sumatra, an area traditionally and religiously known for the philosophy of “Adat Basandi Syarak, Syarak Basandi Kitabullah”.                  This study used a survey method with a qualitative and quantitative analysis approach. Data were collected through a survey of 430 respondents in West Sumatra obtained through multiple random sampling and in-depth interviews with various stakeholders, including politicians, academics, and the general public.                 The results showed that although the majority of West Sumatran people still uphold customary and religious values, rapid social and economic changes had influenced their perceptions of money politics. These findings indicated an increasing acceptance of money politics as a strategy to achieved political power, which had implications for political resilience in West Sumatra. This study highlighted the importance of strengthening political education and democratic values that were in line with local traditions to maintained the integrity of the democratic process in West Sumatra.